2014
DOI: 10.1097/mph.0000000000000226
|View full text |Cite
|
Sign up to set email alerts
|

Genetic Education and Sickle Cell Disease

Abstract: Sickle cell disease (SCD) genetic knowledge is important when individuals make reproductive decisions. This study assessed feasibility and efficacy of delivering basic genetic information to 101 adolescents with SCD. Participants completed a questionnaire to test SCD genetic knowledge at 3 timepoints: before genetic education session (pretest), after the session (posttest), and 6 months later (follow-up). Scores at 3 timepoints were compared by Wilcoxon signed-rank tests, and group differences were compared by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
15
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 12 publications
(15 citation statements)
references
References 28 publications
(29 reference statements)
0
15
0
Order By: Relevance
“…In our broad literature search, there were nine studies that tested educational interventions for persons with SCD (5664), but none included pain as an outcome and thus were excluded in this review.…”
Section: Resultsmentioning
confidence: 99%
“…In our broad literature search, there were nine studies that tested educational interventions for persons with SCD (5664), but none included pain as an outcome and thus were excluded in this review.…”
Section: Resultsmentioning
confidence: 99%
“…For example, it was apparent that when information on the genetic risk for SCD was received, carriers did not accurately understand these risks. Therefore, implementing strategies such as the "teach-back" method may be helpful to confirm that this information has been accurately received (Nutbeam et al, 2017;Porter et al, 2014). This method is shown to be effective in genetic education (Porter et al, 2014;Tluczek et al, 2011).…”
Section: Discussionmentioning
confidence: 96%
“…Therefore, implementing strategies such as the "teach-back" method may be helpful to confirm that this information has been accurately received (Nutbeam et al, 2017;Porter et al, 2014). This method is shown to be effective in genetic education (Porter et al, 2014;Tluczek et al, 2011). Teach-back techniques involve asking participants to use their own words to illustrate their understanding of material discussed (Kripilani, Bengtzen, Henderson, & Jacobsen, 2008).…”
Section: Discussionmentioning
confidence: 99%
“… 4 We identified one study that investigated the efficacy of a clinically delivered, genetic education program for adolescents with SCD. 5 Porter et al used a genetic counseling framework with a candy model strategy to convey genetic risks and found that adolescents were able to grasp the basic genetic inheritance concepts of SCD. Other quantitative studies explored the attitudes and beliefs and desire for reproductive health knowledge on SCD or SCT.…”
Section: Introductionmentioning
confidence: 99%
“…Other quantitative studies explored the attitudes and beliefs and desire for reproductive health knowledge on SCD or SCT. 5–8 Each of these studies was conducted in the United States, except for Melaibari et al's study, which investigated views of young adults in Saudi Arabia on the national premarital screening program of the country. 9 Findings were similar across the board, with studies indicating a general lack of knowledge about reproductive options and sickle cell inheritance, and confusion about adequacy of resources for this information.…”
Section: Introductionmentioning
confidence: 99%